SURVEY OF MOSQUITO SPECIES, COMPOSITION AND BREEDING HABITATS IN FOUR COMMUNITIES OF KADUNA METROPOLIS, NIGERIA - Yayock, H. C.; Osagiede, Nicholas Osazuyi; Bitrus, S.; Gimba, H. S.; Shehu, R. (FUDMA JOURNAL OF SCIENCES, 2021)
A survey on the species composition and breeding habitats of mosquitoes was conducted in four communities of Kaduna metropolis (Nariya, Tudun Wada, Kabala Doki and Sabon Tasha) through intensive bi-weekly sampling collection of larvae for a period of three months. All the randomly selected sampling points were categorized into three habitat types; Domestic Container (DC), Temporary Ground Pool (TGP) and Man-made Reservoir (MMR). All 3rd and 4th instar larvae were harvested and identified using taxonomic keys by Gillies and Coetzee. A total of 6,803 larvae samples were encountered and identified across the four communities. There were thirteen species which fall within the three common genera comprised of Culex species (94.19%), Aedes species (4.8%) and Anopheles (0.10%). Of the thirteen species identified, Culex quinquefasciatus Say, 1823 (72.8%) was significantly high (p0.05) in distribution of mosquitoes among the three habitat types sampled; The study identified medically important mosquito species in the four communities and recommends integrated control measures for these vectors especially in line with National Malaria Control strategy 2016 - 2030 for global reduction of malaria disease
Keywords: Kaduna Metropolis, Culex quinquefasciatus.